Glucose is a pH-dependent motor for sperm beat frequency during early activation. - Nadja Mannowetz (Public Library of Science (PLoS), 2012)
To reach the egg in the ampulla, sperm have to travel along the female genital tract, thereby being dependent on external energy sources and substances to maintain and raise the flagellar beat. The vaginal fluid is rich in lactate, whereas in the uterine fluid glucose is the predominant substrate. This evokes changes in the lactate content of sperm as well as in the intracellular pH (pH(i)) since sperm possess lactate/proton co-transporters. It is well documented that glycolysis yields ATP and that HCO(3)- is a potent factor in the increase of beat frequency. We here show for the first time a pathway that connects both parts. We demonstrate a doubling of beat frequency in the mere presence of glucose. This effect can reversibly be blocked by 2-deoxy-D-glucose, dichloroacetate and aminooxyacetate, strongly suggesting that it requires both glycolysis and mitochondrial oxidation of glycolytic end products. We show that the glucose-mediated acceleration of flagellar beat and ATP production are hastened by a pH(i) ≥7.1, whereas a pH(i) ≤7.1 leaves both parameters unchanged. Since we observed a diminished rise in beat frequency in the presence of specific inhibitors against carbonic anhydrases, soluble adenylyl cyclase and protein kinase, we suggest that the glucose-mediated effect is linked to CO(2) hydration and thus the production of HCO(3)- by intracellular CA isoforms. In summary, we propose that, in sperm, glycolysis is an additional pH(i)-dependent way to produce HCO(3)-, thus enhancing sperm beat frequency and contributing to fertility.